Matched unrelated donor hematopoietic progenitor cell transplantation: A report based on a single registry in India. (2019) - Tiwari, Aseem K; Mishra, Vikash Chandra; Tiwari, Apeksha; Dorwal, Pranav; Gupta, Kapil; Chandra, Dinesh; Raina, Vimarsh
Abst ract: Introduction: Currently, more than 10, 000 matched unrelated donor transplants (MUDT) are performed annually worldwide. India has recorded a significant increase in the number of hematopoietic progenitor cell transplantation (HPCT) centers reporting transplants. The number of HPCTs increases by approximately 10% every year, with 1878 transplants reported by Indian stem cell transplant registries in 2016. However, published outcome data of MUDT in India are scant, with reports limited to autologous and allogenic matched unrelated transplants, which motivated us to present our MUDT data. Aims and objective: To review the operations, and more importantly, the patient outcome data of a new registry in India. Materials and methods: We accessed an Indian HLA donor database with high-resolution HLA typing results of 7682 (until 31st July 2018) volunteer HLA donors. The typing results were uploaded to proprietary software. The search result was considered a "match" when a 10/10 potential HLA match was found. Patients who were found to be alive through mail communication and did not exhibit signs and symptoms of disease were considered to have disease-free survival (DFS). Results: During the six years of operations of the database, 1165 searches resulted in 68 10/10 matches from the registry. Of these, 11 were MUD HPCT records. At a minimum follow-up of almost 11 months, seven recipients continue to exhibit DFS. Conclusions: The patient DFS data prove that even a small registry with slightly more than 7000 donors can yield reasonably good patient outcomes.